Doctor-patient communication: A proposal for continuous improvement in clinical practice - Carrapiço, Eunice (2012)
Introduction: Interpersonal communication skills are fundamental to all clinical practice, but this is especially true in relationshipbased disciplines such as family medicine. Training in communication skills is an integral part of medical education especially during specialty training. Objectives: To develop and test a model for the analysis and training of communication skills in clinical practice based on behavioural elements. Methods: The authors proposed a model for the development of communication skills in clinical practice. This model was developed between 2009 and 2010 from consultations observed in a family practice vocational training clinic. A reflexive observational cycle approach was adopted. This process combined reflexive critical practice, bibliographic study, and the discussion of behavioural elements in clinical communication. Some consultations were recorded on video for this purpose. A selective approach was used to identify aspects of clinical communication distinct from those related to the doctor-patient relationship or with the process of the clinical consultation. The authors intended to describe the pure communication behaviours in depth in order to observe and enhance them. Results: Observation and reflection on consultations revealed 55 behavioural skills. These skills were organized into a model composed of 12 communication skills categories. Four skills were considered central. These included listening, questioning, putting oneself in the patients place, and confirming and reformulating. The remaining skills were opening, observing, leading the consultation, harmonizing, explaining, summarizing, reaching agreement, and concluding. Conclusions: Clinical communication is much more rich and complex that the simple sum of the behavioural components identified. However, the proposed model was found to be relevant and useful for the improvement of doctor-patient communication skills in this setting. It also has been useful for the design of self-assessment exercises and for external assessment using video recording. Successful communication is related to the doctors genuine interest in each patient as a unique person, to the doctors will and motivation to improve their interpersonal communication skills, and to a dedicated effort to improve the large range of complex skills required for effective doctor-patient communication.